Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1155/2014/521380
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Chromosome 9p Status in Renal Cell Carcinoma: A Systematic Review and Quality of the Reported Studies

Abstract: Defining the prognosis of renal cell carcinoma (RCC) using genetic tests is an evolving area. The prognostic significance of 9p status in RCC, although described in the literature, remains underutilised in clinical practice. The study explored the causes of this translational gap. A systematic review on the significance of 9p status in RCC was performed to assess its clinical applicability and impact on clinical decision-making. Medline, Embase, and other electronic searches were made for studies reporting on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The positivity of expression of low molecular weight CAM 5.2, PAX 8, CD 10, vimentin, CAIX and RCC marker and the negativity of CK 7, CK 20, TTF1 and S100 highly supports the proposed diagnosis of mRCC [13,14]. The genomic alterations detected further favored the diagnosis; recent data implicated PBRM1 to be associated with clear cell RCC16 as well as alterations in CDKN2A [15][16][17]. Afterwards, upon reviewing numerous radiological images, no solid renal mass was detected.…”
Section: Discussionmentioning
confidence: 92%
“…The positivity of expression of low molecular weight CAM 5.2, PAX 8, CD 10, vimentin, CAIX and RCC marker and the negativity of CK 7, CK 20, TTF1 and S100 highly supports the proposed diagnosis of mRCC [13,14]. The genomic alterations detected further favored the diagnosis; recent data implicated PBRM1 to be associated with clear cell RCC16 as well as alterations in CDKN2A [15][16][17]. Afterwards, upon reviewing numerous radiological images, no solid renal mass was detected.…”
Section: Discussionmentioning
confidence: 92%
“…However, the application of this genetic information has yet to progress to the clinical setting, and a few would question application of this information in healthcare. A recent systematic review [ 19 ] carried out to assess the quality of studies reporting the significance of 9p chromosomal abnormalities in RCC and to assess whether it could be used as a tool to predict oncological outcomes in RCC. Looking at 11 studies, including a total of 1431 patients, it was found that more work including standardization of techniques were needed to validate the clinical role of 9p status.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of published literature on prognostic value of 9p deletion in RCC has shown that most studies were observational and used a wide variety of molecular and conventional cytogenetic techniques. The studies were mostly old series with no common protocols, which led to a discrepancy in the outcomes and the quality of the studies reviewed [ 4 ].…”
Section: Introductionmentioning
confidence: 99%